Simulating Сarbon Dioxide Emissions when Cultivating Soil - Nozim I. Jabborov; Aleksandr V. Dobrinov; Aleksei P. Mishanov; Anatoliy P. Savelyev (Инженерные технологии и системы, 2025)
Introduction. The urgency of the study is related to the problem of reducing emissions of climate-impacting substances used on agricultural areas. According to current estimates of scientists, 25–40% of climate-impacting gases (especially nitrous oxide and carbon dioxide ) are of soil origin. The methods of soil cultivation together with temperature and humidity significantly affected the emissions of climate-impacting gases from plowed lands. In this regard, mathematical simulation of carbon dioxide emissions when using different methods of soil cultivation is a topical task. Aim of the Study. The study is aimed at developing a mathematical model for determining and forecasting carbon dioxide emissions from soil cultivated with different methods. Materials and Methods. In the study, there were used the methods of mathematical simulation of the carbon dioxide emission process taking into account the data on gas emission assessing through using the chamber and the sensor CDD 24 HTL. Results. A mathematical model has been developed for assessing and forecasting carbon dioxide emission from soil cultivated with different methods. Based on the experimental data, there have been obtained the constant values and angular coefficients characterizing the intensity of carbon dioxide emission in specific conditions of basic moldboard soil cultivation. For the technological process of basic moldboard soil cultivation, the carbon dioxide emission was in the range from 11.3 to 92.4 kg from 1 ha of area (or from 1.13 to 9.23 g per 1 m2 ). Discussion and Сonclusion. The carbon dioxide emission into the atmosphere caused by human activities and by using different methods of soil cultivation in producing crop products has a negative impact on the environment. The soil and climatic features of the region influence the emission values, so these values can vary significantly. This fact requires the study of the emission value for the conditions of a particular region. The study is aimed at improving the methods for assesing and forecasting gas emissions and can be used in crop production.